The Influence of Grit on Nurse Performance with Job Satisfaction and Organizational Commitment as Mediator Variables at X Hospital in South Sumatra - Lisa, Maudina Ainul; Hendra Achmadi (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This study aims to analyze the impact of grit on job satisfaction, organizational commitment, and nurse performance, as well as the effect of grit on nurse performance mediated by job satisfaction and organizational commitment. The study adopts a quantitative descriptive approach with a cross-sectional design. Data were collected through a survey method using a questionnaire, and the sample was purposively selected, consisting of 230 nurses working at RS X, South Sumatra. Data processing and analysis were conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results indicate that grit has a positive and significant direct effect on job satisfaction, organizational commitment, and nurse performance. The study also demonstrates that grit positively and significantly influences nurse performance, partially mediated by job satisfaction, while organizational commitment shows an insignificant effect in mediating the relationship between grit and nurse performance. The managerial implications of this study suggest the need for evaluation the factors that improve nurse performance at RS X, South Sumatra.